SIMULATION OF AN ELECTROMYOGRAPHIC SIGNAL CONVERTER FOR ADAPTIVE ELECTRICAL STIMULATION TASKS - Yeroshenko, Olha; Prasol, Igor; Datsok, Oleh (Sučasnij stan naukovih doslìdženʹ ta tehnologìj v promislovostì (Online), 2021)
The subject matter of the article is an electromyographic signal transducer, which are an integral part of devices for adaptive electrical stimulation of muscle structures based on reverse electromyographic communication. The goal of the work is to study the features, obtaining the corresponding theoretical relationships and computer modeling of a differential biopotential converter, providing amplification of the useful component and suppression of harmful interference, the spectra of which intersect. The following tasks were solved in the article: determining the effect of electrode width and electrode spacing on crosstalk; formation of the electrode-skin model and the input circuit of the transducer, obtaining theoretical relations for calculating the rejection coefficient, construction of the transducer circuit and its computer simulation. The following methods were used – methods of mathematical modeling of processes and technical devices; methods of analysis, structural and parametric synthesis of nonlinear electronic circuits; methods of machine design. The following results were obtained – a biopotential amplifier circuit with tracking feedback on power supply is proposed; modeling of dynamic processes by means of the Multisim program was carried out; on the basis of the constructed model of the electrode-skin input circuit and the obtained analytical relationships, the rejection coefficient of the input circuit of the equivalent circuit is calculated; the requirements for the signal registration module are formulated. Conclusions: The considered version of the electromyographic signal converter circuit based on tracking communication on power supply, effectively rejects 50 Hz common mode noise. On the basis of the constructed equivalent model of the input circuit of the amplifier, the theoretical relation for calculating the rejection coefficient of such amplifiers. The circuit is simulated in the Multisim program, the results confirmed the correctness of its functioning. The requirements for the interelectrode distance and the thickness of the electrodes themselves are also formulated. The results obtained can be used to design complexes for adaptive electrical stimulation.